Trauma-Informed Care in the Massachusetts Child Trauma Project. (May 2016) - Bartlett, Jessica Dym; Barto, Beth; Griffin, Jessica L.; Fraser, Jenifer Goldman; Hodgdon, Hilary; Bodian, Ruth
Child maltreatment is a serious public health concern, and its detrimental effects can be compounded by traumatic experiences associated with the child welfare (CW) system. Trauma-informed care (TIC) is a promising strategy for addressing traumatized children's needs, but research on the impact of TIC in CW is limited. This study examines initial findings of the Massachusetts Child Trauma Project, a statewide TIC initiative in the CW system and mental health network. After 1 year of implementation, Trauma-Informed Leadership Teams in CW offices emerged as key structures for TIC systems integration, and mental health providers' participation in evidence-based treatment (EBT) learning collaboratives was linked to improvements in trauma-informed individual and agency practices. After approximately 6 months of EBT treatment, children had fewer posttraumatic symptoms and behavior problems compared to baseline. Barriers to TIC that emerged included scarce resources for trauma-related work in the CW agency and few mental providers providing EBTs to young children. Future research might explore variations in TIC across service system components as well as the potential for differential effects across EBT models disseminated through TIC.